Pelapisan Hidroksiapatit Di Permukaan Stainless Steel 316L Menggunakan Metode Dip Coating Dengan Variasi Jumlah Hidroksiapatit - Ulfah Naida Marbun; Ahmad Fadli; Silvia Reni Yenti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The 316L stainless steel is widely used as implant, but it still has some downsides such as low biocompatibility and it will release metal ion in the body. Therefore coating the surface of the metal with hydroxyapatite is done to resolve these problems. Coating thickness is an important parameter in the coating process. The purpose of this research is to study the effect of HA amount to the coating thickness. The procedurs in this research are making of HA slurry, substrate preparation, coating process, drying and sintering. The fixed variables in this research are 3 gram of polyethylene glycol, 54 ml of aquades, stirring rate of 300 rpm for 20 hours, immersion time is 10 seconds, drying at 110 °C for 30 minutes, sintering at 700 °C for 1 hour, one time dipping, substrate starilization for 15 minutes, and substrate drying at 110 °C for 10 minutes. The changeable variable is the amount of HA as much as 18 and 24 gram. This study concluded that the more amount of HA used, the thicker coating thickness achieved. The HA coating thickness achieved in this research are in the range of 126-223 μm.Keywords: coating thickness, dip coating, hydroxyapatite, 316L stainless steel.